Chromosomal Variability in Akodon sp. (Rodentia, Cricetidae) - Kasahara, Sanae [UNESP] (1982)
In a sample of 30 specimens of Akodon sp. (Rodentia, Cricetidae), diploid numbers of 2n=24 and 2n=25 along with two mosaic cases with 2n=25/26 and 2n=23/24 were found. The inter and intraindividual chromosome variability of 2n=24, 2n=25 and 2n=25/26 was due to the presence of supernumerary chromosomes. The 2n=23/24 mosaic resulted from elimination of the Y chromosome in somatic cells, the gonads showing a normal XY constitution. Heteromorphism of the X chromosome was also observed. G and C-band patterns of mitotic and meiotic chromosomes are described. © 1982, Japan Mendel Society, International Society of Cytology. All rights reserved.